MECHANISM OF RESTRICTING THE RIGHTS AND FREEDOMS OF CITIZENS AND ORGANIZATIONS IN ORDER TO PROTECT PRIVATE AND PUBLIC INTERESTS - Fedotova, Yuliya; Rezakov, Maxim; Masalskaya, Marina; Polozhentseva, Irina; Zaloilo, Maxim (Revista Inclusiones, 2020)
The purpose of the article is to characterize the legal restriction of the rights and freedoms of citizens and organizations in order to protect private and public interests. In such work were applied such methods as formal legal, sociological, historical, systematic methods, comparison, analysis and synthesis, interpretation of legal norms. The author analysis the concept and content of the restriction of the rights and freedoms of citizens and organizations. A scientific approach is proposed to determine the restriction of the rights and freedoms of citizens and organizations in order to protect private and public interests as a formative element of the legal status of an individual, reflecting the limits, conditions and procedure for the realization of rights and freedoms. Based on the analysis of international acts and Russian constitutional judicial practice, the legal principles and requirements for the application of restrictions on the rights and freedoms of citizens and organizations in order to protect private and public interests are disclosed.